2022
DOI: 10.3390/electronics11182939
|View full text |Cite
|
Sign up to set email alerts
|

A Framework and Method for Surface Floating Object Detection Based on 6G Networks

Abstract: Water environment monitoring has always been an important method of water resource environmental protection. In practical applications, there are problems such as large water bodies, long monitoring periods, and large transmission and processing delays. Aiming at these problems, this paper proposes a framework and method for detecting floating objects on water based on the sixth-generation mobile network (6G). Using satellite remote sensing monitoring combined with ground-truth data, a regression model is esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…( Ma et al., 2019 ) proposed CBAM-GAN generative adversarial network, which can significantly improve the quality of generated images. ( Li et al., 2022 ) adopted MobileNetv3 to detect floating objects on the water surface and CBAM to enhance feature fusion. The experiment showed that the detection accuracy of the improved model increased by 2.9% and the detection speed increased by 55%.…”
Section: Related Workmentioning
confidence: 99%
“…( Ma et al., 2019 ) proposed CBAM-GAN generative adversarial network, which can significantly improve the quality of generated images. ( Li et al., 2022 ) adopted MobileNetv3 to detect floating objects on the water surface and CBAM to enhance feature fusion. The experiment showed that the detection accuracy of the improved model increased by 2.9% and the detection speed increased by 55%.…”
Section: Related Workmentioning
confidence: 99%
“…To address the problem of small targets being easily missed and mistakenly detected in application scenarios, this paper proposes a data augmentation method, STDA (Small Target Data Augmentation, STDA), for small target training using the Mosaic algorithm. The STDA process [41] is shown in Figure 3. The procedure initiates with the fusion of four original images, followed by random scaling down and the application of data augmentation operations, such as flipping and merging.…”
Section: Small Target Data Augmentationmentioning
confidence: 99%